The The Nexus Between “Village” Banking Model & Women’s Financial Inclusion in Zambia (American Journal of Applied Statistics and Economics, 2024)
This study explores the relationship between the ‘Village’ (cooperative microcredit) Banking Model and the financial inclusion of women in Zambia, using the AFRIZAM CO-OPERATIVE as a case study. Multiple regression and correlational analyses were employed as quantitative approaches, while the thematic analysis, elucidated via the saturation strategy, constituted the qualitative approach. The study employed a mixed-method approach, with a sample size of 109 individuals. Findings indicate that co-operative society models significantly promote financial inclusion among women in Zambia. Specifically, savings, access to credit and social capital indicate that holding other factors constant, a 1% increase in each variable significantly increases financial inclusion by 25.5%, 28.1% and 44.3%, respectively. Among the challenges that hinder the financial inclusion of women at Afri-Zam, the study revealed that administrative inefficiencies and inadequate policy support persistently hinder the optimal financial inclusion of women. To mitigate these challenges and augment financial inclusion prospects, the study recommends policy actions that include strengthening savings initiatives among village banking microcredit institutions, enhancing access to credit among women, building and leveraging social capital, addressing administrative inefficiencies by streamlining bureaucratic processes and continuing financial literacy campaigns among women, among others.